2022
DOI: 10.1210/endocr/bqac139
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and COVID-19 Susceptibility and Its Severity: A Two-Sample Mendelian Randomization Study

Abstract: Several observational studies have confirmed the relationship between thyroid hormones and Coronavirus disease 2019 (COVID-19), but this correlation remains controversial. We performed a two-sample Mendelian Randomization (MR) analysis based on the public available largest summary datasets. Summary statistics with 49,269 individuals for free thyroxine (FT4) and 54,288 for thyroid stimulating hormone (TSH) were used as exposure instruments. Genome-wide association studies of the susceptibility (N = 1,644,784), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Intestinal barrier impairment, dysbiosis of gut microbiota, and perturbation of metabolites are prevalent occurrences among individuals with COVID‐19. Extensive research has consistently shown the association between microbiota composition and the morbidity, exacerbation, and mortality rates seen in COVID‐19 patients 51–55 . The gut microbiota facilitates the assessment of sickness severity in individuals with COVID‐19 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal barrier impairment, dysbiosis of gut microbiota, and perturbation of metabolites are prevalent occurrences among individuals with COVID‐19. Extensive research has consistently shown the association between microbiota composition and the morbidity, exacerbation, and mortality rates seen in COVID‐19 patients 51–55 . The gut microbiota facilitates the assessment of sickness severity in individuals with COVID‐19 56 .…”
Section: Discussionmentioning
confidence: 99%
“…This study adhered to the most recent STROBE-MR guidelines. 20,21 For the outcome dataset, we obtained genetic instruments for thyroid cancer (649 cases and 431 controls) from publicly available summary statistics. 22 All datasets are downloadable from the IEU OpenGWAS database (https://gwas.mrcieu.ac.uk/datasets/).…”
Section: Methodsmentioning
confidence: 99%
“…For the exposure (COVID-19 susceptibility, COVID-19 hospitalization, and very severe COVID-19), we employed summary statistics from GWAS of the COVID-19 susceptibility and severity. These data encompassed 38,984 individuals of European ancestry with COVID-19 susceptibility and 1,644,784 controls, 9986 individuals of European ancestry with COVID-19 hospitalization and 1,877,672 controls, and 5101 individuals of European ancestry with very severe COVID-19 and 1,383,241 controls. , For the outcome dataset, we obtained genetic instruments for thyroid cancer (649 cases and 431 controls) from publicly available summary statistics . All datasets are downloadable from the IEU OpenGWAS database ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations